Trend 1997 - 2011. Statistics Canada. CANSIM: Society and Community - Volunteering and Donating | Country: Canada | Province: Nunavut | Table: Summary of charitable donors | Variable: 75th percentile total income of donors | Units: # $CAD, 1997-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-192. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Society and Community - Volunteering and Donating | Country: Canada | Province: Nunavut | Table: Summary of charitable donors | Variable: 75th percentile total income of donors | Units: # $CAD, 1997-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-192. Dataset: Provides data on how Canadians give and receive help directly and through organizations. Statistics are provided on caregiving, unpaid work, unpaid child care, charitable donations, social and emotional support, volunteering, and coaching. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Volunteering, Charitable Contributions